Electrochemical Oxidation of Isopropanol on Platinum-Ruthenium Nanoparticles Studied with Real-Time Product and Dissolution Analytics - Khanipour, Peyman; Speck, Florian; Mangoufis Giasin, Iosif; Mayrhofer, Karl; Cherevko, Serhiy; Katsounaros, Ioannis (ACS Applied Materials and Interfaces, 2020)
The selective electrooxidation of 2-propanol to acetone can be used in fuel cells which, when combined with the transfer hydrogenation of acetone from liquid organic hydrogen carriers, will enable the realization of hydrogen economy without using molecular hydrogen gas for storage and transportation. We study the reaction on platinum and platinum-ruthenium nanocatalysts using unique tools for the real-time characterization of reaction and dissolution products. Acetone is the primary product on all investigated catalysts, and only traces of CO2 form at high potentials. We propose that the reaction occurs on Pt-Ru ensemble sites at low potentials and on Pt-Pt sites at high potentials. Dissolution of surface ruthenium atoms leads to suppression of the process at low overpotential. The main shortcomings to be addressed for an efficient catalyst performance are (a) the narrow potential range in which the bimetallic catalyst is active, (b) the surface poisoning from adsorbed acetone, and (c) the dissolution of ruthenium.
CRIS-Team Scopus Importer:2020-08-28
Keywords: electrocatalysis; electrochemical real-time mass spectrometry; inductively coupled plasma mass spectrometry; isopropanol fuel cells; PtRu nanoparticles; time-resolved analysis